2021
DOI: 10.36834/cmej.71483
|View full text |Cite
|
Sign up to set email alerts
|

A pre-clerkship simulation-based procedural skills curriculum: decreasing anxiety and improving confidence of procedural skill performance

Abstract: Introduction: Pre-clerkship procedural skills training is not yet a standard across Canadian medical school curricula, resulting in limited exposure to procedures upon entering clerkship. While simulated skills training has been documented in the literature to improve performance in technical ability, anxiety and confidence have yet to be investigated despite their documented impact on performance and learning. This study therefore aims to evaluate the effect of pre-clerkship procedural skills training on medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Fortunately, carefully designed content can optimize preparation by reducing cognitive load and positively influencing student engagement and motivation [22]. While manuals [23,24], PowerPoint presentations (PPs) [25,26] and video lectures [27,28] have been used to present various types of knowledge in flipped PS training, instructional theory suggests that PK is better learnt by the observation of a demonstration of the skill being performed [29]. Although demonstration videos (DVs) have been used as pre-skill conceptualisation in simulation-based flipped PS training in a handful of studies [7,8,[30][31][32][33], singly or in combination with other material, only 3 of these reported on objective measures of skills acquisition and presented conflicting results [7,8,31].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, carefully designed content can optimize preparation by reducing cognitive load and positively influencing student engagement and motivation [22]. While manuals [23,24], PowerPoint presentations (PPs) [25,26] and video lectures [27,28] have been used to present various types of knowledge in flipped PS training, instructional theory suggests that PK is better learnt by the observation of a demonstration of the skill being performed [29]. Although demonstration videos (DVs) have been used as pre-skill conceptualisation in simulation-based flipped PS training in a handful of studies [7,8,[30][31][32][33], singly or in combination with other material, only 3 of these reported on objective measures of skills acquisition and presented conflicting results [7,8,31].…”
Section: Introductionmentioning
confidence: 99%
“…It has enhanced learner competence and expertise (Bamford et al, 2018;Greif et al, 2010;Hale et al, 2021;Hayden et al, 2014). Due to these findings, evidence supports the introduction of SBPT to students before clerkships (Battaglia et al, 2021;Omori et al, 2005) to better prepare them to learn in the clinical setting (Battaglia et al, 2021;Remmen et al, 2001).…”
Section: Discussionmentioning
confidence: 85%
“…Simulation-based research conducted over decades is ripe with evidence supporting improved educator and learner satisfaction (Bradley, 2006), learner knowledge and confidence (Battaglia et al, 2021;Laschinger et al, 2008), and competence when assessed on simulators (Hale et al, 2021;Morgan & Cleave-Hogg, 2000). Although most studies support the use of simulation for improved knowledge and skill, only a few studies have shown the effectiveness of transferring knowledge and skill gained in simulation training into clinical practice (Hill et al, 2011).…”
Section: Effectiveness Of Simulation For Acquiring Procedural Expertisementioning
confidence: 99%
“…Thus, Remmen et al assumed that skills training better prepares students for clinical clerkships [ 41 ]. Students were found to be less anxious and more confident at the bedside with procedural training in the pre-clerkship period [ 42 ]. Therefore, SBPT is recommended to be integrated as a longitudinal training course into medical curricula [ 43 ], starting from the pre-clerkship period [ 44 ].…”
Section: Introductionmentioning
confidence: 99%